Mucocutaneous Manifestations in HIV-Infected Patients and Their Relationship to CD4 Lymphocyte Counts - Mina Mirnezami; Nader Zarinfar; Masoomeh Sofian; Bahareh Botlani Yadegar; Hoda Rahimi (Scientifica)
Background. More than 90% of human immunodeficiency virus- (HIV-) infected patients show at least one mucocutaneous manifestation during the course of their disease. The frequency, pattern, and associated factors of these complications vary among different populations. Objective. This study was planned to evaluate the frequency of cutaneous presentations in HIV-infected patients and their association with the count of CD4 cells. Methods. A cross-sectional study was conducted on eighty-four HIV-positive patients, who attended the Behavior Consultation Center of Arak University of Medical Sciences. All subjects had a complete physical examination by an expert dermatologist. Further diagnostic procedures were performed, if necessary. Counts of CD4 were determined using flow cytometry. Results. From 84 patients who enrolled in this study, 95.2% manifested at least one type of mucocutaneous lesions. The most common presentation was xerosis, followed by seborrheic dermatitis, herpes simplex, and oral candidiasis. Oral candidiasis and furuncle were significantly associated with decrease in CD4 cell counts. Conclusions. Cutaneous manifestations are common in HIV-positive patients, some of which (oral candidiasis and furuncle) could be applicable as useful clinical indicators to predict the immune status of the patients. Therefore, regular skin examinations are recommended as routine HIV-infected patients’ healthcare programs.